Preparation and Properties of Novel Magnetic Rhizopus oryzae Biomass Particles for Removal of Congo Red from Aqueous Solution - Fu, Yong-Qian; Zhu, Huayue; Yin, Longfei; Jiang, Ru; Li, Xin (Asian Journal of Chemistry, 2015)
Novel magnetic Rhizopus oryzae biomass particles (m-RBps) were prepared successfully and characterized by XRD, SEM and FT-IR. The ability of magnetic Rhizopus oryzae biomass particles to remove congo red from aqueous solutions has been carried out as a function of adsorbent dose (0.6-3 g/L), initial congo red concentration (5-80 mg/L) and contact time. An amount of 1 g/L of magnetic Rhizopus oryzae biomass particles could remove more than 95 % of the dye from 20 mg/L congo red solution. The amount of congo red adsorbed per unit weight of magnetic Rhizopus oryzae biomass particles increased from 6.3 to 65.19 mg with increasing concentration from 5 to 80 mg/L. In the kinetic study, the pseudo-second order kinetic model described the process of congo red adsorption on magnetic Rhizopus oryzae biomass particles at low congo red concentration (5-50 mg/L) very well. Adsorption kinetic studies also revealed that three stages in the adsorption process. Both film diffusion and intra-particle diffusion simultaneously operated during adsorption at low congo red concentrations (5-50 mg/L). Intra-particle diffusion is the sole rate-limiting step at high congo red concentration (80 mg/L). Isotherm modeling revealed that the Langmuir equation could better describe congo red adsorption on magnetic Rhizopus oryzae biomass particles compared with Freundlich models. The magnetic Rhizopus oryzae biomass particles may be a promising candidate of efficient, low cost, convenient separation under magnetic field.